Eosinophilic granulomatosis with polyangiitis: an unusual cause of stroke. Issue 4 (5th April 2022) - Huckenpahler, Alison Lee; Iqbal, Harris; Gallan, Alexander; Jha, Pinky
Abstract : Stroke has become increasingly common with the rise in hyperlipidaemia, hypertension and other metabolic disorders. In this case, a 69-year-old man with several weeks of non-specific symptoms and no history of metabolic disorders presents with unilateral weakness and supraventricular tachycardia. Kidney biopsy confirmed a diagnosis of eosinophilic granulomatosis with polyangiitis. He responded well to rituximab infusions.